Hierarki Iblis dalam Pandangan Kristen Analisis Buku the Complete Book of Demonolatry Karya S. Connolly - Hutajulu, Muhammad Irgi Septiana; Harahap, Elly Warnisyah; Paralihan, Hotmatua (ANWARUL, 2023)
The purpose of this study is to find out how the Christian view of the Devil's Hierarchy, and how the Devil's Hierarchy forms according to the book The Complete Book Oof Demonolatry, and how the Qur'an views the Devil's Hierarchy. This type of research uses library research through a normative theological approach. This thesis explores data from two sources, namely primary and secondary sources, the primary source is The Complete Book of Demonolatry by S. Connolly and secondary sources, namely articles, websites, books, literature, documents and the Bible. The research results show that Satan regulates the hierarchy evil spirits who inhabit the air and who help him to rule the kingdom of darkness. the term "Devil's Hierarchy" is not specifically mentioned in the Bible. However, several verses give views of the existence of different levels or roles among the demons, which can sometimes be interpreted as hierarchies. The forms of the Hierarchy of Demons are very diverse, there are many different classifications of each Occultist or Bishop. But in the Qur'an there are no verses that tell about the existence of a ruler or leader of Satan. This means that according to the Islamic Religion, this Devil's Hierarchy is not something that must be studied or understood more deeply.